A comparative evaluation of certain processing procedures (cooling, equilibration and thawing) in deep freezing of cattle and buffalo semen under tropical climate* - DHAMI, A J; SAHNI, K L (The Indian Journal of Animal Sciences, 2013)
The effects of bulls, cooling rales (15,30,60 and 120 min from 10oC W 5oC vs 120 min from 28oC to 5oC), equilibration periods (0,1,2 and 3 hr), thawing rales (40oC/60 sec, 60oC/15 sec and 80oC/5 sec) and Their interactions were studied for cryopreservation of semen of 3 Friesian and 3 Murrah bulls. The prefreeze motility of both cattle and buffalo spenn was significantly influenced by faster cooling rates from 10oC butnot by equilibration periods. The post-thaw motilily and incuoation survival (1 hr) of cattle sperm increased significantly with each increase in cooling time, equilibration period and thawing rate, whereas in buffalo semen the effect of cooling rates was not so marked, except 15 min, and all other rates yielded significantly better post-thaw motilitÂ  compared to routine cooling from 28oC. Buffalo spem were also not benefited by increasmg equilibration period over 1 hr. The post-thaw incubation survival of buffalo sperm (11.28%)compared to cattle sperm (18.75%) was also much less. The bull X cooling, bull X eqililibration and cooling X equilibration interactions were significant for motility of cattle sperm only. In general, buffalo sperm could be frozen satisfactorily within 30-60 min of collection by directly cooling the semen straws from 10oC even without equilibration at 5oC, but cattle spcm appeared more susceptible to such aprotocol and requiredroutine slow cooling from 28Â°C. Thawing of straws at 60oC for 15 sec appeared practicable for both the species in tropical conditions.